The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1088/2053-1583/ab15ec
|View full text |Cite
|
Sign up to set email alerts
|

Operando study of water vapor transport through ultra-thin graphene oxide membranes

Abstract: The paper reports operando study of ultra-thin (50 nm) graphene oxide membranes by grazing incidence x-ray scattering in air dehumidification experiments. Absorption of water vapors in GO layers follows a modified Kelvin equation revealing condensation in an elastic slit, while desorption of water is limited by a few outer GO layers providing bottleneck restrictions to water transport and resulting in classical H2-type isotherms. GO interlayer distances (d) vary in range from 7.2 Å to 11.5 Å depending on parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…[5] In many studies, the driving force of vapor permeation is assumed to be a gradient of water pressure on opposite sides of membranes. [77,78] This pressure gradient (mbar) is significantly smaller compared to the pressure gradient (1-20 bar) used in pressure-driven filtration experiments. Since the permeance of membranes is usually expressed in units which include pressure, the small gradient of pressure due to difference in humidity between feed and permeate streams in pervaporation experiments results in calculations of huge values, e.g., ≈80 000 L/(m 2 bar h) even for quite common water flux.…”
Section: Discussionmentioning
confidence: 99%
“…[5] In many studies, the driving force of vapor permeation is assumed to be a gradient of water pressure on opposite sides of membranes. [77,78] This pressure gradient (mbar) is significantly smaller compared to the pressure gradient (1-20 bar) used in pressure-driven filtration experiments. Since the permeance of membranes is usually expressed in units which include pressure, the small gradient of pressure due to difference in humidity between feed and permeate streams in pervaporation experiments results in calculations of huge values, e.g., ≈80 000 L/(m 2 bar h) even for quite common water flux.…”
Section: Discussionmentioning
confidence: 99%
“…These results should allow precise control of the density of sheets deposited by the LB or Langmuir-Schaefer (LS) procedures. Graphene oxide is also extremely attractive for air and natural gas dehumidification and an operando study of ultrathin (50 nm) membranes by GID during air dehumidification has been reported [193]. It was found that the absorption of water vapor in graphene oxide layers follows a modified Kelvin equation similar to condensation in an elastic slit, whereas desorption of water is limited by a few outer layers.…”
Section: Liquid Interfacesmentioning
confidence: 99%
“…(4) The linear adsorption isotherm (or non-adsorption) for all gases on the surface of MXene lamellar membranes is neglected. (5) The mass transfer resistance of gas within the porous AAO layer is neglected due to its much large pore size [10,26].…”
Section: Theoretical Models Of Transport Mechanismmentioning
confidence: 99%
“…Processes 2019, 7, x; doi: FOR PEER REVIEW 4 of 17 (5) The mass transfer resistance of gas within the porous AAO layer is neglected due to its much large pore size [10,26]. (6) Gas mixture (hydrogen and nitrogen) transport through the membrane is under ideal conditions on which the actual separation factor is equal to the ideal selectivity and pure gas permeance is equal to the mixture permeance.…”
Section: Theoretical Models Of Transport Mechanismmentioning
confidence: 99%